Effect of Opuntia ficus-indica mucilage in the ecological extraction, drying, and storage of eggplant anthocyanins - Chávez Gutiérrez, Miguel; Utrilla-Coello, Rubí Guadalupe; Soto-Castro, Delia (Journal of Food Processing and Preservation, 2017)
In this study, Opuntia ficus-indica mucilage was evaluated as a protecting agent of anthocyanins from Solanum melongena L. by spray drying. The performance of mucilage as a protectant was evaluated using the ratio of the percent of Radical Scavenger Activity (RSA) to the concentration of anthocyanin [C]. The results showed that, in presence of mucilage, after 4 months the %RSA/C was preserved in 73% of wet samples and in 64% of spray dried samples, compared to wet samples without mucilage, where %RSA/C preserved was 30%. Additionally, it was found that acidified mucilage (0.4%) could be used as a viable extracting and encapsulating agent, thereby avoiding the use of organic solvents and the generation of associated residues. Also, the acidification modified the rheological behavior of mucilage from non-Newtonian to Newtonian, improving the spray drying process and preserving the %RSA/[CA] in 96% of samples after drying. Microcapsules observed by SEM showed a worm-like morphology.
Keywords: Mucílago; Antocianinas; Secado por aspersión